Development and Assessment of Solid Lipid Nanoparticles of Bergamot Essential Oil - Mude, Gaurav; Singune, Shantilal (Journal of Neonatal Surgery, 2025)
Bergamot essential oil (BEO) administration by Solid Lipid Nanoparticles (SLNPs) is an innovative approach to improving the therapeutic potential and stability of the oil. Unfortunately, bergamot essential oil has a number of drawbacks, including a high volatility, low solubility, and a vulnerability to environmental deterioration, despite its well-known antibacterial, antioxidant, and anti-inflammatory characteristics. An intriguing option is SLNPs, which encase BEO in a lipid matrix and provide advantages such as controlled release, increased bioavailability, and protection from environmental influences. The researchers in this work used a heated homogenization and ultrasonication technique to create SLNPs that contained BEO. Size, shape, encapsulation effectiveness, zeta potential, and polydispersity index (PDI) were the parameters measured for the nanoparticles. Verification of physicochemical stability was carried out using differential scanning calorimetry (DSC) and Fourier-transform infrared spectroscopy (FTIR), which showed that BEO was successfully encapsulated and was compatible with the lipid matrix. A prolonged release profile was shown in in vitro release tests, which greatly reduced the evaporation of volatile chemicals. In comparison to free BEO, SLNPs loaded with BEO showed improved efficacy against common pathogens in antimicrobial tests. Tests for cytotoxicity validated the compositions' biocompatibility, lending credence to their medicinal promise. In light of the shortcomings of BEO, this study demonstrates the effectiveness of SLNPs, opening the door for their use in the food, cosmetic, and pharmaceutical sectors. Additional in vivo investigations into the feasibility and therapeutic use of SLNPs as a vehicle for bergamot essential oil administration are warranted in light of these results.